2021
DOI: 10.1093/mnras/stab3611
|View full text |Cite
|
Sign up to set email alerts
|

The terrestrial planet formation around M dwarfs: insitu, inward migration, or reversed migration

Abstract: Terrestrial planets are commonly observed to orbit M dwarfs with close-in trajectories. In this work, we extensively perform N-body simulations of planetesimal accretion with three models of in-situ, inward migration and reversed migration to explore terrestrial formation in tightly compact systems of M dwarfs. In the simulations, the solid disks are assumed to be 0.01% of the masses of host stars and spread from 0.01 to 0.5 AU with the surface density profile scaling with r−k according to the observations. Ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 77 publications
2
4
0
Order By: Relevance
“…Our Gaussian model also seems to agree (within a factor of a few) with the inward and reversed migration models for terrestrial planetary formation from Pan et al (2022), which found similar planet occurrence rates around M dwarfs. Their reversed migration model found a peak at intermediate radii, and subsequent decrease in occurrence, though their calculated occurrence with stellar radius relation is flatter than what we observe and peaks around 0.2 M e , which corresponds to radii significantly below the observed peak in the planet distribution.…”
Section: A Nonuniform Occurrence Around Small Starssupporting
confidence: 79%
See 2 more Smart Citations
“…Our Gaussian model also seems to agree (within a factor of a few) with the inward and reversed migration models for terrestrial planetary formation from Pan et al (2022), which found similar planet occurrence rates around M dwarfs. Their reversed migration model found a peak at intermediate radii, and subsequent decrease in occurrence, though their calculated occurrence with stellar radius relation is flatter than what we observe and peaks around 0.2 M e , which corresponds to radii significantly below the observed peak in the planet distribution.…”
Section: A Nonuniform Occurrence Around Small Starssupporting
confidence: 79%
“…Adopting the values of σ A from lightkurve and our power-law fit allows for a similarly good fit with a Gaussian that peaks at a similar (or slightly higher) stellar radius (≈0.42 R ⊕ ) and an amplitude at its peak around 6 planets per star as opposed to 3 planets per star. This does not necessarily contradict the estimation of λ ≈ 2.5 planets per star from Dressing & Charbonneau (2015) for similar reasons as the Gaussian model with σ A = 0, but does contradict, e.g., Pan et al (2022), which, with theoretical formation and migration models, did not find such a large-amplitude peak in planetary occurrence at intermediate radii, or indeed such a high planetary occurrence around any systems unless all of the planets were formed in situ.…”
Section: A Nonuniform Occurrence Around Small Starssupporting
confidence: 50%
See 1 more Smart Citation
“…Additionally, planet formation simulations conducted by Raymond et al (2007) found that it may be difficult for M dwarf accretion disks to form terrestrial planets larger than ∼0.3 M ⊕ , potentially decreasing the probability of M dwarfs participating in habitable planet formation. Alternatively, M dwarf planets that form beyond the snow line and migrate inward may retain substantial water content on the crust and in the mantle (Ogihara & Ida 2009;Unterborn et al 2018;Pan et al 2022). Furthermore, ice-rich planetary embryos may migrate interior to the snow line that would otherwise have been blocked by the presence of a giant planet (Izidoro et al 2015;Bitsch & Savvidou 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the core-accretion model of planet formation, planets grow from initial over densities (known as cores) in a protoplanetary disk, which accrete dust and gas from the surrounding disk. Models in which initial cores grow through the accretion of ~1-km-sized solid bodies (called planetesimals) ( 8 10 , 39 ), or by accreting pebble-sized material ( 40 , 41 ), predict that very low-mass stars are only capable of forming compact systems of rocky planets on short-period orbits. The maximum mass of planets formed through core accretion in simulations of the planetesimal-driven scenario around low-mass stars is about 5M ( 9 ), and 3M in the pebble accretion–driven scenario ( 40 , 41 ).…”
Section: Comparison With Planet Formation Modelsmentioning
confidence: 99%